2018
DOI: 10.18553/jmcp.2018.24.11.1130
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Technician Management of Stable, In-Range INRs Within a Clinical Pharmacy Anticoagulation Service

Abstract: BACKGROUND: There is increasing demand on pharmacist time within clinical pharmacy services, and pharmacy technicians are a crucial resource for expanding pharmacy practice. OBJECTIVE: To assess the safety and effectiveness of pharmacy technician management of stable, in-range international normalized ratio (INR) results compared with usual care. METHODS: This retrospective, longitudinal, noninferiority cohort study was conducted at an integrated health care delivery system with a centralized anticoagulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…One study demonstrated similar time in therapeutic range using pharmacy technicians to assess international normalized ratios (INRs) among patients receiving chronic warfarin compared with pharmacists (83.3% and 77.7% in the technician and pharmacist groups, respectively, P < 0.05). 22 Furthermore, although there was no difference in thromboembolism between groups, there was lower bleeds and all-cause mortality in the technician group. 22 Another study conducted at the Veteran's Affairs demonstrated that more than 50% of tasks performed by pharmacists within their anticoagulation services, including telephone follow-up to patients with in-range INRs, could be handled by pharmacy technicians, resulting in greater than $55,000 annual cost-savings.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One study demonstrated similar time in therapeutic range using pharmacy technicians to assess international normalized ratios (INRs) among patients receiving chronic warfarin compared with pharmacists (83.3% and 77.7% in the technician and pharmacist groups, respectively, P < 0.05). 22 Furthermore, although there was no difference in thromboembolism between groups, there was lower bleeds and all-cause mortality in the technician group. 22 Another study conducted at the Veteran's Affairs demonstrated that more than 50% of tasks performed by pharmacists within their anticoagulation services, including telephone follow-up to patients with in-range INRs, could be handled by pharmacy technicians, resulting in greater than $55,000 annual cost-savings.…”
Section: Discussionmentioning
confidence: 83%
“…The CPCRS has demonstrated improved surrogate, clinical, and economic outcomes among the patients enrolled. [20][21][22] Patients in the EPIC Healthy Planet registry are categorized in "active" or "surveillance" mode based on whether they have attained all of their cardiovascular risk reduction goals (lipids and BP, appropriate statin intensity, adherent to medications). Patients in "surveillance" mode get yearly lipid monitoring.…”
Section: Practice Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2006 wage premiums for pharmacy technicians in the US have fluctuated in a manner and to a degree similar to those experienced by the median of "all occupations" in the US economy. Yet, what has been asked of pharmacy technicians in terms of expanded job roles [4][5][6][7][8][9][10][11][12] and regulatory requirements [21][22][23] has increased over this time. While one would expect to see positive wage premiums as a result of these increases in job roles and requirements, this was not observed in our analysis, and is consistent with the findings of other researchers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy technicians support pharmacists in dispensing medications, performing clinical functions needed to improve the outcomes of mediation use [4][5][6], and to perform a number of administrative functions which assist in the operations of a pharmacy [7]. Pharmacy technicians have been asked to increasingly take on roles that had previously been exclusively performed by pharmacists, including reviewing medications and checking the work of other technicians prior to dispensing [8,9], taking medication histories [10], managing warfarin therapy within a clinical pharmacy anticoagulation service [11] and immunization delivery [12]. Pharmacists depend upon a stable labor market of pharmacy technicians to support them in optimizing patient health outcomes.…”
Section: Introductionmentioning
confidence: 99%